The United States Food and Drug Administration's Platform Technology Designation to Expedite the Development of Drugs - Sarfaraz K. Niazi (MDPI AG, 2024)
Drug development costs can be significantly reduced if proven "platform" technologies are allowed to be used without having to validate their use. The most recent US Food and Drug Administration (FDA) guideline brings more clarity, as well as a greater focus on the most complex technologies that can now be used for faster drug development. The FDA has highlights the use of lipid nanoparticles (LNPs) to package and deliver mRNA vaccines, gene therapy, and short (2-20 length) synthetic nucleotides (siRNA). Additionally, monoclonal antibody cell development is targeted. The FDA provides a systematic process of requesting platform status to benefit from its advantages. It brings advanced science and rationality into regulatory steps for the FDA's approval of drugs and biologicals.